EFFECTS OF FINANCIAL INCLUSION ON ECONOMIC GROWTH IN NIGERIA (Journal of Contemporary Issues in Accounting, 2022)
EFFECTS OF FINANCIAL INCLUSION ON ECONOMIC GROWTH IN NIGERIAThis study investigated the effect of financial inclusion on economic growth in Nigeria from 1981-2021, the objectives of the study were to, Analyze the effect of total bank loans on economic growth in Nigeria; determine the effect of bank branches on economic growth in Nigeria; Evaluate the impact of commercial banks deposit on economic growth in Nigeria; and Evaluate the impact of automated teller machine services on economic growth in Nigeria. Ordinary least squared (OLS) method of data analysis was adopted because of its Best Linear Unbiased Estimators (BLUE) properties. The variables used were sourced from Central Bank of Nigeria Statistical Bulletin. The variables used were total bank loans, bank branches, commercial banks deposit, and gross fixed capital formation. The collected data were sourced from central bank of Nigeria (CBN) statistical bulletin 2021 The study adopted the unit root test, co-integration approach, as well as Error Correction Mechanism. E- View software was used for the analysis. The study found that: Total bank loan has negative and significant effect on economic growth in Nigeria (t, -2.198595, p=0.0389). This result implies that Total bank loan has not favored the economic growth in Nigeria. Bank branches have positive and significant effect on economic growth in Nigeria (t, 2.549937, p=0.0191). This implies that Bank branches has contributed significantly to economic growth in Nigeria. Commercial bank deposit has positive and significant effect on economic growth in Nigeria; (t, 3.103610, p=0.0009). The implication of this result is that Commercial bank deposit has positively affected the economy of this country. The study recommends that, Banks should be very careful the way and manner they give out loan to customers, they should make sure that corresponding collateral is presented before loan should be issues out and again the purpose of the loan should be define properly. Increase in the number of bank branches to support their economic activities. The number currently in circulation is limited and banks should deploy more POS devices to strategic places like shops, churches, schools, hospitals, institutions and fuel stations for easy access to financial transactions.
Keywords: total bank loans; bank branches; commercial banks deposit; gross fixed capital formation